Características farmacognósticas del fruto de pernettya prostrata (cav.) dc. (macha macha) procedente de la región Ayacucho - Braul Porras, Edgard Gilmer (2016)
This research aimed to determine the characteristics of the fruit farmacognósticas of Pernettya prostrata. The fruits were collected from the Ayacucho region and identified by the Herbarium Truxillense of the National University of Trujillo. The farmacognósticas characteristics were conducted according to the methodology of Miranda, where the macroscopic characteristics, physicochemical and phytochemical screening of fresh fruits were determined. The results showed that the fresh fruits have a diameter and average weight of 10 mm ± 0.776 and 0.018 ± 10.1 g respectively. Also these fruits are purple, fleshy texture, smooth surface, suigeneris odor, circular and soft consistency. The physicochemical characteristics found were: brix (9.8° ± 0.1), refractive index (1.347 ± 0.001), pH (5.24 ± 0.003), dry weight (3.02 g ± 0.077), total solids (0.44 g ± 0.0027), ash total (4.76 ± 0.076%), water insoluble ash (2.44% ± 0.09), acid insoluble ash (1.52% ± 0.062) and humidity (17.2 ± 1.19%). The phytoconstituents found were: oils and fat, lactones, triterpenes and steroids, phenolics, anthocyanidins, flavonoids, catechins, amino acids, reducing sugars, tannins and saponins.